2014
DOI: 10.3168/jds.2013-7435
|View full text |Cite
|
Sign up to set email alerts
|

How do cattle respond to sloped floors? An investigation using behavior and electromyograms

Abstract: On dairy farms, flooring is often sloped to facilitate drainage. Sloped floors have been identified as a possible risk factor for lameness, but relatively little is known about how this flooring feature affects dairy cattle. Ours is the first study to evaluate the short-term effects of floor slope on skeletal muscle activity, restless behavior (measured by number of steps), and latency to lie down after 90 min of standing. Sixteen Holstein cows were exposed to floors with a 0, 3, 6, or 9% slope in a crossover … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
3

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 31 publications
0
14
3
Order By: Relevance
“…Regardless of floor type or presentation method, cattle did not experience fatigue (as measured by changes in MPF and MA) over the 1 h of standing. Similarly, when SEMG were used on cows to evaluate muscle fatigue, there was no indication of fatigue when comparing MPF and MA values at the start and end of 90 min standing (Rajapaksha and Tucker, 2014) and 1 h of standing (Rajapaksha and Tucker, 2015). In the current study, significant MPF reduction was observed on the concrete surfaces without corresponding MA increase; thus, this change did not meet the definition of fatigue used by Luttman et al (2000).…”
contrasting
confidence: 78%
See 2 more Smart Citations
“…Regardless of floor type or presentation method, cattle did not experience fatigue (as measured by changes in MPF and MA) over the 1 h of standing. Similarly, when SEMG were used on cows to evaluate muscle fatigue, there was no indication of fatigue when comparing MPF and MA values at the start and end of 90 min standing (Rajapaksha and Tucker, 2014) and 1 h of standing (Rajapaksha and Tucker, 2015). In the current study, significant MPF reduction was observed on the concrete surfaces without corresponding MA increase; thus, this change did not meet the definition of fatigue used by Luttman et al (2000).…”
contrasting
confidence: 78%
“…Eight self-adhesive bipolar surface electrodes (3M Red Dot Repositionable Electrodes, Ag/AgCl) were attached on the skin over the middle gluteal muscle (an extensor of the hip joint and abductor of the leg that controls hip movements) and the biceps femoris muscle (extensor of the hip and stifle and flexor of the stifle) muscle on both right and left sides of the cow. Details of skin preparation and electrode placement are explained in our previous work (Rajapaksha and Tucker, 2014). An electromyography telemetric system (Megawin Biomonitor ME 6000, Mega Electronics Ltd., Kuopio, Finland) was used to record SEMG readings during both static and dynamic muscle contractions.…”
Section: Behavioral Observations: Stepping Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The research on responses to standing can be divided into 2 methods of presentation: evaluation of flooring features where all 4 legs are on standard surfaces (e.g., concrete or rubber), and where only 1 leg experienced something different, such as pain or exposure to alternative flooring. Experiments that present treatments under all 4 legs have used stepping rate to examine the effect of standing time (Cooper et al, 2007), floor slope (Rajapaksha and Tucker, 2014), or surface compressibility (Krebs et al, 2011;Chapinal and Tucker, 2012). In all of these experiments, steps increased over time, but no differences were observed between flooring treatments.…”
Section: Introductionmentioning
confidence: 99%
“…Fatigue in other livestock species has been measured via EMG (Girsch et al, 1995;Robert et al, 2000;Lee et al, 2013;Rajapaksha and Tucker, 2014), but these studies did not explore the biological characteristics of the muscle responsible for fatigue. Therefore, the objectives of this study were to use a RAC diet feeding model to induce muscle exhaustion in barrows, measure muscle fiber activity via EMG, and relate differences in exhaustion to muscle fiber type characteristic differences.…”
Section: Introductionmentioning
confidence: 99%